Analysis of Cultural Aspects and Their Influence on Internal Audit Effectiveness: A Literature Review - Brian Audika; Astrini Aning Widoretno (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
To increase organizational performance, the internal audit function must contribute information that may be used to make informed decisions. The discussion also stressed how contingency considerations affect the efficacy and quality of internal audit. This study analyses the literature on contingencies with a cultural background based on the contingency basis. This study employs a systematic review methodology to identify existing information and gaps. In addition to describing the function of culture in businesses, this study demonstrates how internal audit contributes to sound decision-making and enhances organizational performance. This research contributes to understanding culture's role in the internal audit's quality and effectiveness.